The pain of children with sickle cell disease: the nursing approach - Lívia Maria Nunes Campelo; Nayara Fernandes Oliveira; Juliana Macêdo Magalhães; Alcineide Mendes de Sousa Julião; Fernanda Cláudia Miranda Amorim; Magda Coeli Vitorino Sales Coelho (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To describe how nurses identify the pain in children with sickle cell disease (SCD) and to list the strategies used by them in the evaluation and control of pain. Method: This is a qualitative, descriptive and exploratory research, performed through semi-structured interviews with 13 nurses. The interviews were transcribed and after this process the qualitative data were organized according to thematic analysis. Results: This study showed that the nurses can identify pain in children with SCD from the signals they emit, such as: constant crying, restlessness, facial expressions and verbal reports. Pain is difficult to evaluate due to the lack of instruments, such as a pain scale. For pain control they use emotional support, promotion of comfort and the administration of drugs prescribed by the doctor. Final considerations: The nurses recognize the pain of the child and use pharmacological and non-pharmacological methods to control it but have difficulties to assess it.